Bud viability in perennial grasses: Water stress and defoliation effects - Flemmer, Andrea Cecilia (2002)
Effects of the timing and frequency of defoliation under different levels of soil water availability were evaluated on bud metabolic activity and subsequent outgrowth in the desirable (i.e., palatable) Stipa clarazii Ball. and S. tenuis Phil. in competition with the undesirable (i.e., unpalatable) S. gynerioides Phil. Field studies on these native, perennial tussock grasses were conducted from 1995 to 1997 in temperate, semiarid Argentina. Our working hypotheses were 1) axillary bud activation and subsequent tillering are lower under water stress than under higher soil moisture conditions in S. clarazii, S. tenuis, and S. gynerioides, 2) when compared to undefoliated controls, activation, and subsequent outgrowth of axillary buds reach similar or greater values in S. clarazii and S. tenuis after early (vegetative stage of development), but not late (during internode elongation) defoliations or increased defoliation frequency (vegetative+ during internode elongation) during each growing cycle. Additionally, it was expected that the greatest reduction of axillary bud metabolic activity and outgrowth would ocurr on plants defoliated twice, and 3) axillary bud activation and succeeding tillering are greater in the undefoliated S. gynerioides when the desirable species are defoliated than when they remain undefoliated. With a few exceptions, our results led us to reject all 3 hypotheses. Responses of axillary buds were in general specific to the species and treatments, to sampling time, and to the cumulative effects of previous treatments. This makes predictions of plant responses of these species under natural field conditions difficult, where they are often defoliated under water stress.